Character Education Values in Mathematics Story Problem Solving Activities in Elementary School - Sunarni, Sunarni; Usodo, Budi; Chumdori, Chumdori (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
This study describes character values in mathematics learning. The purpose of the research is to describe the character values of independence, critical reasoning, and creativity. The type of research is descriptive qualitative. Data collection through: observation, questionnaires, and interviews. The result of the research is the activity of solving mathematical story problems raises character values, namely being able to: recognize and realize self-development needs; process, build links, analyze, evaluate, and conclude; and generate ideas and look for alternative solutions. The conclusion of the research is that learning mathematics on story problem solving material can build independent character values, critical reasoning, and creativity.